2020
DOI: 10.1158/1538-7445.pedca19-pr07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PR07: GD2 is a macrophage checkpoint molecule and combined GD2/CD47 blockade results in synergistic effects and tumor clearance in xenograft models of neuroblastoma and osteosarcoma

Abstract: The use of anti-GD2 antibodies for neuroblastoma (NBL) has resulted in enhanced survival, but many patients still relapse and ultimately die of their disease. Additionally, despite expression of GD2 on osteosarcoma (OS), anti-GD2 antibodies have not proven widely effective in that disease. Enhancing the efficacy of anti-GD2 antibodies could result in improved patient outcomes. CD47 is the dominant “Don’t Eat Me” signal expressed by cancer cells to inhibit macrophage phagocytosis. Blocking CD47 with antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A combination of anti-CD47 antibody with dinutuximab in OS xenografts showed significant tumour growth delay in osteosarcoma xenografts as well as decrease in metastatic burden in a pulmonary metastatic model, whereas single agent anti-GD2 or anti-CD47 had no anti-tumour effects. The investigators hypothesised that GD2 is a macrophage checkpoint capable of inhibiting tumour cell phagocytosis [22]. This combination is now being evaluated in a clinical trial for recurrent osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of anti-CD47 antibody with dinutuximab in OS xenografts showed significant tumour growth delay in osteosarcoma xenografts as well as decrease in metastatic burden in a pulmonary metastatic model, whereas single agent anti-GD2 or anti-CD47 had no anti-tumour effects. The investigators hypothesised that GD2 is a macrophage checkpoint capable of inhibiting tumour cell phagocytosis [22]. This combination is now being evaluated in a clinical trial for recurrent osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested that GD2 serves as a macrophage checkpoint or "don't eat me" signal between neuroblasts and TAM. [31] The interplay of GD2-ligation with 14G2a and macrophage and MDSC clearance may therefore be related to immunologic activation via FcR binding, via cell-cell interaction changes mediated by blockade of GD2-macrophage signaling, or by complement binding. Notably, 7 of 15 14G2a mice lived without morbidity beyond cessation of antibody administration at day 100, while none of the mice in the control groups survived beyond day 70.…”
Section: Discussionmentioning
confidence: 99%
“…124 Since macrophages frequently infiltrate metastatic NB tumors 127 and since CD47 is frequently expressed on high-risk tumors, the combination of dinutuximab with an anti-CD47 antibody was evaluated in pediatric xenograft models of NB and the combination was found to be synergistic. 128 This combination will soon be tested in children. 128…”
Section: Cd47mentioning
confidence: 99%